School-Based Intervention Programs for Preventing Obesity and Promoting Physical Activity and Fitness: A Systematic Review - Yuksel, Hidayet Suha (Int J Environ Res Public Health, 2020)
With the significant decrease in physical activity rates, the importance of intervention programs in the schools, where children spend a significant part of the day, has become indisputable. The purpose of this review is to systematically examine the possibility of school-based interventions on promoting physical activity and physical fitness as well as preventing obesity. A systematic approach adopting PRISMA statement was implemented in this study. Three different databases (2010–2019) were screened and primary and secondary school-based intervention programs measuring at least one variable of obesity, physical activity, or physical fitness were included. The risk of bias was assessed using the validated quality assessment tool for quantitative studies. Among 395 potentially related studies, 19 studies were found to meet the eligibility criteria. A general look at the studies examined reveals that among the outcomes, of which most (18/19) were examined, a significant improvement was provided in at least one of them. When the program details are examined, it can be said that the success rate of the physical activity-oriented programs is higher in all variables. School-based interventions can have important potential for obesity prevention and promotion of physical activity and fitness if they focus more on the content, quality, duration and priority of the physical activity.